2010
DOI: 10.1002/ab.20366
|View full text |Cite
|
Sign up to set email alerts
|

Sweetened blood cools hot tempers: physiological self-control and aggression

Abstract: Aggressive and violent behaviors are restrained by self-control. Self-control consumes a lot of glucose in the brain, suggesting that low glucose and poor glucose metabolism are linked to aggression and violence. Four studies tested this hypothesis. Study 1 found that participants who consumed a glucose beverage behaved less aggressively than did participants who consumed a placebo beverage. Study 2 found an indirect relationship between diabetes (a disorder marked by low glucose levels and poor glucose metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 46 publications
3
55
1
Order By: Relevance
“…However, this may have been due to the relatively small sample size (123 participants) in their study. The present finding that low self-control significantly predicts aggression concurs with the results of other studies (DeWall et al, 2011;Hamama & Ronen-Shenhav, 2012;Kim et al, 2008;Ozdemir et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, this may have been due to the relatively small sample size (123 participants) in their study. The present finding that low self-control significantly predicts aggression concurs with the results of other studies (DeWall et al, 2011;Hamama & Ronen-Shenhav, 2012;Kim et al, 2008;Ozdemir et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, low self-control as a mediator between situational variables and aggression is supported by a wealth of research (DeWall et al, 2011;Li, Li, & Newman, 2013;Runions, 2013;Winstok, 2009). Low self-control could also play a mediating role in predicting aggression and violence (DeWall et al, 2011;Ozdemir, Vazsonyi, & Cok, 2013;Qu & Zou, 2009) as it has been shown to play a mediating role in situational variables (e.g., parenting processes) that predict aggression (Ozdemir et al, 2013). Other studies have demonstrated the mediating effect of parental behavior on aggression (Kim et al, 2008;Ronen, Abuelaish, Rosenbaum, Agbaria, & Hamama, 2012).…”
mentioning
confidence: 98%
“…Poor glucose tolerance is a core feature of some conditions, such as diabetes. Other research has also shown that elevated diabetic symptoms relate to greater aggressiveness (12). Future work may explore whether poor glucose tolerance represents a risk factor for intimate partner violence.…”
Section: Discussionmentioning
confidence: 89%
“…Numerous studies have found a relationship between low glucose levels and poor self-control (8). For example, when glucose levels are low, people have more difficulty controlling their attention (9), regulating their emotions (10,11), and overriding their aggressive impulses (12). Some evidence suggests that low glucose levels might even increase the risk of violent criminal behavior, including spousal abuse (13).…”
Section: Self-controlmentioning
confidence: 99%
“…Self-control allows for emotional coping (e.g., regulating moods so as to increase happiness, Baumeister, Bratslavsky, Muraven, & Tice, 1998;Finkel & Campbell, 2001;Gailliot, Schmeichel, & Baumeister, 2006;Gailliot, Schmeichel, & Maner, 2006;Muraven & Slessareva, 2003;Schmeichel, Demaree, Robinson, & Pu, 2005;Schmeichel, Vohs, & Baumeister, 2003;Shamosh & Gray, 2006;Vohs, Baumeister, & Ciarocco, 2005) and is intrinsically tied with glucose metabolism (DeWall, Baumeister, Gailliot, & Maner, 2008;DeWall, Gailliot, Deckman, & Bushman, 2009;Fairclough & Houston, 2004;Gailliot, 2008Gailliot, , 2009bGailliot, , 2009dGailliot, Hildebrandt, Eckel, & Baumeister, 2009;Gailliot, Peruche, Plant, & Baumeister, 2009;Masicampo & Baumeister, 2008). A survey across nations indicated that the ability to cope is a primary determinant of happiness (Haller & Hadler, 2006).…”
Section: Happiness As Concomitant With Available Energy-a Review Of Tmentioning
confidence: 99%